The effect of repetition on text cohesion A study of Arabic poems by Kurdish scholars - Hisham Faleh Hamed; Nihad Nader Hamad (Zanco Journal of Humanity Sciences)
In this research we tried to identify the phenomenon of repetition and its role in the consistency of speech in the Arabic poems of the poets of the Kurds, it is consistency that ensures the consistency of the text and distinguish it from the text, which is a set of tools, conditions and linguistic foundations available in each language, which makes the parts and diaspora of text and speech coherent consistent with some , the measure and standard used in consistency is only its interest in the phenomenon and the external form of the text, and Take care of objective study and verification of the means by which it achieves the specificity of continuity and verbal connection, and this binding and arrangement of sentences and phrases takes the standard of what appears to be the surface elements shown in a picture and language panel from which the previous leads to the subsequent , and repetition is a purely linguistic phenomenon through which the total verbal correlation of the text is achieved through a set of prominent formal linguistic phenomena leading to the cohesion and harmony of the text.